Short-term (<8 weeks) high-intensity interval training in diseased cohorts - Blackwell, James E.M.; Doleman, Brett; Herrod, Philip; Ricketts, Samuel; Phillips, Bethan E.; Lund, Jonathan N.; Williams, John P. (Lippincott, Williams & Wilkins, 2018)
Background & Aim: Exercise training regimes can lead to improvements in measures of cardiorespiratory fitness (CRF), improved general health, and reduced morbidity and overall mortality risk. High intensity interval training (HIIT) offers a time-efficient approach to improve CRF in healthy individuals, but the relative benefits of HIIT compared to traditional training methods are unknown in across different disease cohorts. Methods: This systematic review and meta-analysis compares CRF gains in randomised controlled trials of short-term (<8 weeks) HIIT vs. either no exercise control (CON) or moderate continuous exercise training (MCT) within diseased cohorts. Literature searches of the following databases were performed: MEDLINE, EMBASE, CINAHL, AMED, and PubMed (all from inception to 1st December 2017), with further searches of Clinicaltrials.gov and citations via Google Scholar. Primary outcomes were effect upon CRF variables; VO2peak and Anaerobic Threshold (AT). Results: Thirty-nine studies met the inclusion criteria. HIIT resulted in a clinically significant increase in VO2peak compared with CON (mean difference (MD) 3.32 ml∙kg-1∙min-1; 95% CI 2.56 to 2.08). Overall HIIT provided added benefit to VO2peak over MCT (MD 0.79 ml∙kg-1∙min-1; 95% CI 0.20 to 1.39). The benefit of HIIT was most marked in patients with cardiovascular disease when compared to MCT (VO2peak (MD 1.66 ml∙kg-1∙min-1; 95% CI 0.60 to 2.73); AT (MD 1.61 ml∙kg-1∙min-1; 95% CI 0.33 to 2.90)). Conclusions: HIIT elicits improvements in objective measures of CRF within 8 weeks in diseased cohorts compared to no intervention. When compared to MCT, HIIT imparts statistically significant additional improvements in measures of CRF, with clinically important additional improvements in VO2peak in cardiovascular patients. Comparative efficacy of HIIT vs MCT combined with an often reduced time commitment may warrant HIIT’s promotion as a viable clinical exercise intervention.